PENYULUHAN SERVICE EXCELLENCE DALAM PENINGKATAN KUALITAS PELAYANAN WISATA ALAM GUNUNG DAGO PARUNG PANJANG - Simamora, Vera; Pradana, Triandi; Kovalenko , Neswa; Vanit, Familia (Education and Talent Development Center of Indonesia, 2025)
This community service activity was initiated in response to the expressed needs of the local partner, namely the management of Gunung Dago Nature Tourism, Parung Panjang. Based on preliminary discussions with the management, it was identified that while the number of tourist visits has been increasing, this growth has not been matched by the human resource capacity to deliver services in accordance with tourism standards. The partner indicated an urgent need to enhance the capacity of local tourism actors, particularly in understanding and applying the principles of service excellence. Furthermore, the partner acknowledged a lack of awareness in delivering quality service, especially in handling visitor complaints. Key aspects such as responsiveness, empathy, and professional appearance (grooming) have not yet been prioritized in daily service practices. This situation has contributed to low visitor satisfaction and suboptimal destination image. Accordingly, this program aimed to equip tourism personnel with essential knowledge and skills in delivering excellent service through participatory approaches, including education and training. The implementation method consisted of three main stages: (1) preparation, involving coordination, material development, and preliminary survey; (2) a service excellence workshop focused on communication and service ethics; and (3) interactive training through simulations and role-playing. A total of 10 participants were involved, selected based on their direct roles in the destination’s service chain. Evaluation was conducted using a mixed-methods approach, combining pre- and post-tests (quantitative) with direct observation and feedback (qualitative). The results indicated a significant improvement in participants’ cognitive understanding and service skills. Most participants demonstrated higher test scores and positive behavioral changes, including more courteous, responsive, and communicative service. The tourism management expressed satisfaction with the program and committed to implementing improved service standards. This activity contributes practically to community empowerment and theoretically to the development of participatory training models in tourism-based community service programs.